2016
DOI: 10.3847/0004-637x/832/2/187
|View full text |Cite
|
Sign up to set email alerts
|

THE MASSIVE PROTOSTELLAR CLUSTER NGC 6334I AT 220 au RESOLUTION: DISCOVERY OF FURTHER MULTIPLICITY, DIVERSITY, AND A HOT MULTI-CORE

Abstract: We present VLA and ALMA imaging of the deeply-embedded protostellar cluster NGC6334I from 5 cm to 1.3 mm at angular resolutions as fine as 0.′′ 17 (220 AU). The dominant hot core MM1 is resolved into seven components at 1.3 mm, clustered within a radius of 1000 AU. Four of the components have brightness temperatures > 200 K, radii ∼ 300 AU, minimum luminosities ∼ 10 4 L ⊙ , and must be centrally heated. We term this new phenomenon a "hot multi-core". Two of these objects also exhibit compact free-free emission… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(132 citation statements)
references
References 100 publications
10
122
0
Order By: Relevance
“…Figure 1 shows the detections of CH 3 OCH 2 OH in the 0.2 Band 7 data (black) toward MM1 convolved to the spectral resolution of the observations, and with a 2.4 km s −1 linewidth (red). The position chosen for analysis (J2000 17:20:53.373, −35:46:58.14) lies ∼400 au west of the brightest continuum peak, denoted MM1b by Brogan et al (2016). The spectra were converted from Jy/beam to K intensity scale in each spectral window using the beam sizes listed in Table 1.…”
Section: Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the detections of CH 3 OCH 2 OH in the 0.2 Band 7 data (black) toward MM1 convolved to the spectral resolution of the observations, and with a 2.4 km s −1 linewidth (red). The position chosen for analysis (J2000 17:20:53.373, −35:46:58.14) lies ∼400 au west of the brightest continuum peak, denoted MM1b by Brogan et al (2016). The spectra were converted from Jy/beam to K intensity scale in each spectral window using the beam sizes listed in Table 1.…”
Section: Spectroscopymentioning
confidence: 99%
“…The ring-like appearance of the molecular emission toward MM1 is due to the high dust continuum opacity (> 1) and brightness temperature of the 1 mm dust continuum emission toward the dust peaks (> 100 K Brogan et al 2016). Toward the continuum peaks, the high dust opacity attenuates the line emission from the backside of the region, and the high background continuum brightness temperature compared to the line excitation temperature of the transitions shown here (of order 100-200 K) leads to weaker line emission (lower excitation lines are seen in absorption against the continuum peaks).…”
Section: Spatial Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 12 new 1.3 cm detections, with a median peak intensity of 0.42 mJy beam −1 , are sufficiently weak that these are the first (published) data with the sensitivity to detect them. Sub-mJy emission at 1.3 cm (at kiloparsec distances) can be due to either free-free emission from protostellar winds/jets or hypercompact H II regions, or alternatively the Rayleigh-Jeans tail of dust emission (see, for example, Brogan et al 2016). In Section 3.3, we discuss the morphology of the 1.3 cm continuum emission and its relationship to the target EGO for individual sources, and compare with other cm-λ data where possible.…”
Section: 3 CM Continuum Emissionmentioning
confidence: 99%
“…In past decades, radio emission with negative spectral indices at centimeter wavelengths has been reported in several YSO jets, such as the triple radio source in Serpens (Rodríguez et al 1989, Rodríguez-Kamenetzky et al 2016, HH 80-81 (Martí et al 1993), IRAS 16547−4247 (Garay et al 1996;Rodríguez et al 2005), W3(H 2 O) (Wilner et al 1999), L778-VLA6 (Girart et al 2002), DG Tau (Ainsworth et al 2014), NGC6334I-CM2 (Brogan et al 2016), and OMC-2 FIR 3 (Osorio et al 2017) suggesting a non-thermal origin for the emission. In a recent radio survey of the southern hemisphere, Purser et al (2017) found at least 10 new candidates to present non-thermal emission.…”
Section: Introductionmentioning
confidence: 99%